Comparison of physicomechanical properties of films prepared from organic solutions and aqueous dispersion of Eudragit RL - Sadeghi, F. (Tehran University of Medical Sciences, 2011)
BACKGROUND AND THE PURPOSE OF THE STUDY: Mechanical properties of films prepared from aqueous dispersion and organic solutions of Eudragit RL were assessed and the effects of plasticizer type, concentration and curing were examined. METHODS: Films were prepared from aqueous dispersion and solutions of Eudragit RL (isopropy alcohol-water 9:1) containing 0, 10 or 20% (based on polymer weight) of PEG 400 or Triethyl Citrate (TEC) as plasticizer using casting method. Samples of films were stored in oven at 60°C for 24 hrs (Cured). The stress-strain curve was obtained for each film using material testing machine and tensile strength, elastic modulus, %elongation and work of failure were calculated. RESULTS AND MAJOR CONCLUSION: The films with no plasticizer showed different mechanical properties depending on the vehicle used. Addition of 10% or 20% of plasticizer decreased the tensile strength and elastic modulus and increased %elongation and work of failure for all films. The effect of PEG 400 on mechanical properties of Eudragit RL films was more pronounced. The differences in mechanical properties of the films due to vehicle decreased with addition of plasticizer and increase in its concentration. Curing process weakened the mechanical properties of the films with no plasticizer and for films with 10% plasticizer no considerable difference in mechanical properties was observed before and after curing. For those with 20% plasticizer only films prepared from aqueous dispersion showed remarkable difference in mechanical properties before and after curing. Results of this study suggest that the mechanical properties of the Eudragit RL films were affected by the vehicle, type of plasticizer and its concentration in the coating liquid.